Revisão taxonômica dos gêneros Artines Godman, 1901 e Panca Evans, 1955 (Hesperiidae, Hesperiinae, Moncini) - Medeiros, Adalberto Dantas de, 1989- (2019)
Orientador: Prof. Dr. Olaf Hermann Hendrik Mielke